Analisis Pentad Dramatistik dalam Pemasaran Pariwisata Budaya di Tiktok: Studi Kasus Pacu Jalur, Indonesia - Gilbert Johan Martin Sinaga (Journal of Tourism Sciences, Technology and Industry, 2026)
TikTok has become an increasingly important platform for cultural tourism marketing and destination image formation in the digital era. This study aims to examine how Pacu Jalur, a traditional cultural event and tourism destination in Indonesia, is represented on TikTok by Destination Management Organizations (DMOs), destination influencers, and participants in viral trends. Employing a qualitative approach, the study integrates multimodal analysis with Kenneth Burke’s dramatistic pentad framework. The dataset consists of 30 purposively selected TikTok videos, including 10 videos from the official Pacu Jalur Indonesia account, 10 influencer videos using the hashtag #pacujalur, and 10 videos associated with the viral trend #aurafarming. The findings reveal that DMOs represent Pacu Jalur as a collective cultural heritage that emphasizes authenticity, local identity, and cultural legitimacy. In contrast, destination influencers construct more personalized representations by positioning individual experiences at the center of the narrative, thereby generating higher levels of audience engagement. Meanwhile, participants in the #aurafarming trend reconstruct Pacu Jalur through a process of symbolic appropriation that is more flexible and increasingly detached from its original cultural context. The study demonstrates that representations of Pacu Jalur on TikTok are not singular but are continuously negotiated through different communication motives, actor interests, and platform logics. It concludes that TikTok functions as a co-creative arena of cultural tourism meaning-making, where multiple actors participate in shaping destination images. These findings contribute to the growing literature on digital tourism and provide practical implications for the management and marketing of cultural tourism in social media environments.